2013
DOI: 10.1111/ans.12244
|View full text |Cite
|
Sign up to set email alerts
|

Is extended thromboprophylaxis necessary in elective colorectal cancer surgery?

Abstract: We have demonstrated excellent compliance with in-hospital thromboprophylaxis. Hence, we have low VTE rates in-particular, post-discharge VTE. The infrequency of post-discharge VTE means that the cost-effectiveness of extended prophylaxis might be questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Reasons for exclusion are in Figure . Eleven articles reported the incidence of VTE at 3 months (primary outcome) following surgery . However, we were able to find 13 articles that reported the incidence of VTE at 1 month from surgery (secondary outcome).…”
Section: Resultsmentioning
confidence: 93%
“…Reasons for exclusion are in Figure . Eleven articles reported the incidence of VTE at 3 months (primary outcome) following surgery . However, we were able to find 13 articles that reported the incidence of VTE at 1 month from surgery (secondary outcome).…”
Section: Resultsmentioning
confidence: 93%
“…Hata et al reported no symptomatic VTEs within 7 days of surgery in 619 Japanese patients given FPX after CRC surgery [10]. Other studies have reported that the incidence of symptomatic VTE within 30 days of CRC surgery in patients receiving LMWH or UFH range from 0 to 1.8% [11,12,13]. FPX significantly reduces the incidence of VTE in patients undergoing major abdominal surgery with IPC [5], and it is as effective as perioperative LMWH in patients undergoing high-risk abdominal surgery [4].…”
Section: Discussionmentioning
confidence: 99%
“…Our study focussed on patients in an ERAS programme who were undergoing surgery for Stage I--III colon cancer, and it emphasizes the need for randomized trials of prolonged VTE prophylaxis for these patients before making national recommendations. Chandra et al [19] found, in a single-centre study, a similar low risk of post-discharge symptomatic VTE after colorectal cancer surgery without prolonged VTE prophylaxis, but within an ERAS programme. The differences in risk of VTE observed by us and Chandra et al, and the studies [5,6,16] on which the national guidelines [9,10] are based, may possibly be the result of use of an ERAS programme, with early mobilization.…”
Section: Discussionmentioning
confidence: 86%